Irradiation-enhanced α′ precipitation in model FeCrAl alloys. (15th April 2016) - Edmondson, P.D.; Briggs, S.A.; Y.Yamamoto,; Howard, R.H.; Sridharan, K.; Terrani, K.A.; Field, K.G.
Abstract: Model FeCrAl alloys with varying compositions (Fe(10–18)Cr(10–6)Al at.%) have been neutron irradiated at ~ 320 to damage levels of ~ 7 displacements per atom (dpa) to investigate the compositional influence on the formation of irradiation-induced Cr-rich α ′ precipitates using atom probe tomography. In all alloys, significant number densities of these precipitates were observed. Cluster compositions were investigated and it was found that the average cluster Cr content ranged between 51.1 and 62.5 at.% dependent on initial compositions. This is significantly lower than the Cr-content of α ′ in binary FeCr alloys. Significant partitioning of the Al from the α ′ precipitates was also observed. Graphical abstract: